A6.5 Synovial Lymphoid Structures Support Epstein-Barr Virus Persistence and Autoreactive Plasma Cell Infection in Rheumatoid Arthritis. (25th February 2013) - Croia, Cristina; Serafini, Barbara; Bombardieri, Michele; Kelly, Stephen; Humby, Frances; Severa, Martina; Rizzo, Fabiana; Coccia, Eliana Marina; Migliorini, Paola; Aloisi, Francesca; Pitzalis, Costantino
Abstract : Objectives: Rheumatoid arthritis (RA) is associated with an increased Epstein-Barr virus (EBV) blood DNA load, a robust immune response to EBV and cross-reactive circulating antibodies for viral and self-antigens. However, the role of EBV in RA pathogenesis remains elusive. Here we investigated the relationship between synovial EBV infection, ectopic lymphoid structures (ELS) and immunity to citrullinated self and EBV proteins. Methods: Latent and lytic EBV infection was investigated in 43 RA synovial tissues characterised for presence/absence of ELS and 11 OA samples by RT-PCR, in situ hybridisation and immunohistochemistry/immunofluorescence. Synovial production of anti-citrullinated proteins (ACPA) and anti-citrullinated EBV peptides (VCP1/VCP2) antibodies was investigated in situ or in vivo in the SCID/RA chimeric model. Results: EBV dysregulation was observed exclusively in ELS+ RA, but not OA, synovia as revealed by presence of EBV latent [LMP2A, EBV-encoded small RNA (EBER)] transcripts and EBER+ cells and immunoreactivity for EBV latent (LMP1, LMP2A) and lytic (BFRF1) antigens in ELS-associated B cells and plasma cells, respectively. Importantly, 20% of synovial plasma cells producing ACPA were infected with EBV. Furthermore, ELS-containing RA synovia transplanted into SCID mice supported production of ACPA and anti-VCP1/VCP2 antibodies cross-recognised by ACPA. Analysis of CD4+ and CD8+ T-cell localisation and granzyme B expression suggests that EBV persistence in ELS-containing synovia is favoured by exclusion of CD8+ T cells from B-cell follicles and impaired CD8-mediated cytotoxicity. Conclusions: We demonstrated active EBV infection within ELS in the RA synovium that appears to contribute to local growth and differentiation of ACPA-reactive B cells.